2014
DOI: 10.1002/ppul.23073
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐utility analysis of daily versus intermittent inhaled corticosteroids in mild‐persistent asthma

Abstract: Summary Introduction Despite the many benefits that have been demonstrated by the continuous administration of inhaled corticosteroids (ICS) in persistent asthma, a new strategy for mild-asthma is emerging, consisting of using intermittent or as-needed ICS treatment in conjunction with short-acting beta2 agonists in response to symptoms. However, no previous studies have reported an economic evaluation comparing these two therapeutic strategies. Methods A Markov-type model was developed in order to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
(52 reference statements)
0
32
0
Order By: Relevance
“…Most of the 18 studies included originated from the United States, followed by the UK, Colombia, the Netherlands, Canada, Germany, Hong Kong, and Venezuela (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 18 studies included originated from the United States, followed by the UK, Colombia, the Netherlands, Canada, Germany, Hong Kong, and Venezuela (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed a mixed population, although only the results restricted to pediatric patients were considered. The asthma type and severity of the included studies differed, including allergic, persistent, acute, and chronic asthma.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (16%) did not report any funding sources. Most of the CEA studies using effectiveness evidence (7/8, 87.5%) (7,15,16,22,25,31) reported that the interventions were cost-effective, while only 4 out of 9 (44.4%) (18,20,28,32) CEA studies using efficacy evidence were cost-effective.…”
Section: Discussionmentioning
confidence: 97%
“…Limiting inhaled corticosteroids in asthmatic children to the dose needed to achieve good clinical outcome while minimizing side effects is an important goal, and has given rise to investigation of intermittent dosing strategies . Rodriguez‐Martinez et al found that treating patients with recurrent wheezing or mild persistent asthma with daily inhaled corticosteroids results in higher gain in quality adjusted life years (QALY) compared to intermittent treatment . Sidoroff et al reported that regular inhaled corticosteroid use for longer than 6 months in children aged less than 6 years was associated with decreased bone mineral density in the lumbar spine; the amount of the cumulative dose until age 12 was correlated with the amount of decrease in femoral bone mineral density .…”
Section: Asthmamentioning
confidence: 99%
“…17 Rodriguez-Martinez et al found that treating patients with recurrent wheezing or mild persistent asthma with daily inhaled corticosteroids results in higher gain in quality adjusted life years (QALY) compared to intermittent treatment. 18 Sidoroff et al reported that regular inhaled corticosteroid use for longer than 6 months in children aged less than 6 years was associated with decreased bone mineral density in the lumbar spine; the amount of the cumulative dose until age 12 was correlated with the amount of decrease in femoral bone mineral density. 19 Petsky et al studied asthmatic children randomized to use of fractional exhaled nitric oxide (FeNO) monitoring as a treatment guide, and found that use of FeNO was associated with decreased severe exacerbations.…”
Section: Asthma Managementmentioning
confidence: 99%